2006
DOI: 10.1128/iai.01891-05
|View full text |Cite
|
Sign up to set email alerts
|

Type III Secretion-Dependent Modulation of Innate Immunity as One of Multiple Factors Regulated byPseudomonas aeruginosaRetS

Abstract: Mutation of retS (rtsM) of Pseudomonas aeruginosa strain PA103 reduces its virulence in both ocular and respiratory murine models of infection. In vitro, retS mutants exhibit loss of the ExsA-regulated type III secretion system (TTSS), reduced twitching motility, and a decrease in association with, invasion of, and survival within corneal epithelial cells. In addition, transcription of multiple other virulence genes is positively and negatively affected by retS mutation. Since our published data show that ExoU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
(67 reference statements)
3
28
0
Order By: Relevance
“…A peripheral ring infiltrate, which we have previously reported to require ExoU, was observed only in those eyes infected with bacteria expressing intact exoU (Zolfaghar et al, 2006).…”
Section: The Phospholipase Domain Of Exou Is Required For Effects On supporting
confidence: 46%
See 4 more Smart Citations
“…A peripheral ring infiltrate, which we have previously reported to require ExoU, was observed only in those eyes infected with bacteria expressing intact exoU (Zolfaghar et al, 2006).…”
Section: The Phospholipase Domain Of Exou Is Required For Effects On supporting
confidence: 46%
“…We have previously shown that ExoU is involved in the ability of P. aeruginosa to colonize the cornea in vivo and to cause pathology (Lee et al, 2003) which involves inhibition of phagocyte infiltration of the central cornea (Zolfaghar et al, 2006). This followed our earlier work showing that ExoU was responsible for the acute cytotoxicity of cytotoxic strains of P. aeruginosa towards mammalian cells in vitro (Finck-Barbancon et al, 1997;Fleiszig et al, 1997).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations